Pengembangan Strategi Pendidikan Pada Era Transformasi Digital Dan Tantangannya Di Masyarakat - Heru Widoyo (Journal on Education, 2024)
Technology plays an important role in our lives, and has brought humans into the digital era. This change certainly has an influence on lifestyles that cannot be separated from electronic devices in everyday life. In fact, this change in civilization is aimed at making it easier for humans to carry out any activity and work. However, it turns out that this has an impact that is not only positive but also has a negative impact as well. The positive impact is that we can easily access learning resources and can get various information quickly. Meanwhile, the negative impact is that our children will see and be influenced by various sources of bad information, for example pornography, acts of violence, bullying or even narcotics. This of course must inspire all groups, including the government, parents and educators, to immediately become aware and pay more serious attention to the impact of this digital transformation. The more sophisticated the development of digital technology, the greater its influence in various fields, including culture, economics, politics and security maintenance. Education as one of the main pillars of national progress certainly plays a very important role. With the spirit of togetherness in building the nation, of course we can all direct this technological transformation to make it better and more useful.